(3cTa GdXdGe Yf hLhg TQGFY GdESdGes - (3eMSf Hf eQJVi Hf bGSe, J (B1238 (3g`s ((3Nda Hf edG EHQGgjes)
(3ChdgG (B:s
(3GdaUd GdKGdK aj UdGI GdcSha(B...s
(3BNQgG (B:s
(3hCeG GdNHQ GdOGd Ydi LhGR GdML Yf GdMj eY GTJcGdg Ydi UdGI(B... (3aeG Jhge HYVge aj GdGSJOGd Hg aj GdebGe(B... (3ZjQ eMdg(B... (3hjfaY Hg ceG faY HCUdg aj cd HGH hbO aQZ ef JQJjHg eDdag(B... (3hgPG gh GdeLdO GdKGdK ef eLdOGJ GdUdhGJ hGdSGHY ef eLdOGJ GdcJGH(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis